Voltage Regulation in Power Distribution System using Dynamic Voltage Restorer - Depally Srinivas; Rajendar P.; Naveen G.; Manisha Kumari; Jain Abhishek (E3S Web of Conferences, 2023)
In the entire power system we are having different levels of voltages. The voltages are depending on the Generation, Transmission and Distribution. In this Different levels the sudden changes of voltages are occur due to various reasons. But the voltage changes at distribution shows the impact on consumers. So to protect the consumers from sudden voltage changes the DVR technique is used. Which is the most popular technique and it gives the best results, here we are taking induction motor as a load for voltage changes three phase short circuit faults are taking. In this paper the proposed system has been modeled and simulated using the MATLAB/SIMULINK environment and simulation results discussed